1985
DOI: 10.1083/jcb.101.5.1724
|View full text |Cite
|
Sign up to set email alerts
|

Retention of membrane proteins by the endoplasmic reticulum.

Abstract: We have used a monoclonal antibody specific for a hydrocarbon-induced cytochrome P450 to localize, by electron microscopy, the epitope-specific cytochrome P450. The cytochrome was found in the rough and smooth endoplasmic reticulum (ER) and the nuclear envelope of hepatocytes. Significant quantities of cytochrome P450 were not found in Golgi stacks. We also could not find any evidence of Golgi-associated processing of the Asn-linked oligosaccharide chains of two well-characterized ER membrane glycoprotein enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 38 publications
(45 reference statements)
1
19
1
Order By: Relevance
“…Regeneration of Golgi stacks over time in these peripheral sites would reestablish secretory flow from the ER to the Golgi and result in "Golgi fragmentation." the ER (Brands et al, 1985;Persson et al, 1992). Nevertheless, it is possible that Golgi enzymes spend only short periods of time passing through the ER, and therefore are difficult to detect there.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of Golgi stacks over time in these peripheral sites would reestablish secretory flow from the ER to the Golgi and result in "Golgi fragmentation." the ER (Brands et al, 1985;Persson et al, 1992). Nevertheless, it is possible that Golgi enzymes spend only short periods of time passing through the ER, and therefore are difficult to detect there.…”
Section: Discussionmentioning
confidence: 99%
“…Productivity growth has decreased in almost all of the major sectors of the economy. Within the major sectors, the Bureau of Labor Statistics (BLS) looked at specific industry-level performance and found that three-quarters of the industries in their sample had declines in productivity growth (2).…”
Section: October I986mentioning
confidence: 99%
“…The constructed T7-DAD1 cDNA complemented the tsBN7 cells (data not shown), indicating that the T7 fused DAD1 protein has a normal DAD1 function. As a marker of the ER, we used P450 (M1), which is a well known membrane protein localized in the ER (Brands et al 1985;Yamamoto et al 1985;Matsumoto et al 1986). T7-DAD1 cDNA was introduced into the mammalian expression vector pcDEB.…”
Section: Dad1 Is Colocalized With P450 (M1)mentioning
confidence: 99%